2019
DOI: 10.1016/j.brs.2018.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation intensity influences motor cortex plasticity

Abstract: Background: Vagus nerve stimulation (VNS) paired with forelimb motor training enhances reorganization of movement representations in the motor cortex. Previous studies have shown an inverted-U relationship between VNS intensity and plasticity in other brain areas, such that moderate intensity VNS yields greater cortical plasticity than low or high intensity VNS. However, the relationship between VNS intensity and plasticity in the motor cortex is unknown. Objective: In this study we sought to test the hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 50 publications
7
54
0
Order By: Relevance
“…Previous studies have demonstrated that VNS during rehabilitative training improves recovery of motor function in several models of brain injury (Khodaparast et al, 2016, 2014; Hays et al, 2014a,b, 2016; Meyers et al, 2018; Morrison et al, 2019). The therapeutic effects of pairing VNS with motor rehabilitation persist even after the cessation of stimulation, suggesting that the VNS-induced plasticity and learning are long-term (Khodaparast et al, 2014; Hays et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that VNS during rehabilitative training improves recovery of motor function in several models of brain injury (Khodaparast et al, 2016, 2014; Hays et al, 2014a,b, 2016; Meyers et al, 2018; Morrison et al, 2019). The therapeutic effects of pairing VNS with motor rehabilitation persist even after the cessation of stimulation, suggesting that the VNS-induced plasticity and learning are long-term (Khodaparast et al, 2014; Hays et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Rats were trained on a skilled motor task, as in previous studies [15][16][17]23]. The task was an automated lever pressing task, in which the animal was required to learn to reach outside of a cage and press a lever twice in rapid succession.…”
Section: Motor Behavioral Testingmentioning
confidence: 99%
“…The task was an automated lever pressing task, in which the animal was required to learn to reach outside of a cage and press a lever twice in rapid succession. The behavior apparatus consisted of an acrylic cage, with a slot in the front right for access to a lever that was positioned 1 (inside) to 2 cm (outside) away from inside the edge of the chamber [15][16][17]23] ( Fig. 2a).…”
Section: Motor Behavioral Testingmentioning
confidence: 99%
“…Rats were trained on a skilled motor task, as in previous studies (Hays et al, 2013;Hulsey et al, 2016Hulsey et al, , 2019Morrison et al, 2019). The task was an automated lever pressing task, in which the animal was required to learn to reach outside of a cage and press a lever twice in rapid succession.…”
Section: Motor Behavioral Testingmentioning
confidence: 99%